Profile of gestational breast cancer patients at RSUD Dr. Soetomo Surabaya from January 2022 – December 2024 - Adidharma, I Made Ary; Suprabawati, Desak Gede Agung; Susilo, Dwi Hari (Edelweiss Applied Science and Technology, 2025)
Gestational breast cancer is defined as breast cancer diagnosed during pregnancy or within one year after childbirth. Breast cancer is one of the most frequently diagnosed malignancies during pregnancy. This research aims to describe the profile of patients with gestational breast cancer undergoing treatment at RSUD dr. Soetomo Surabaya during the period from January 2022 to December 2024. This study is a descriptive research with a retrospective design to determine the characteristics of patients with gestational breast cancer from January 2022 to December 2024. During this period, four patients underwent treatment at RSUD dr. Soetomo Surabaya, with an age range of 31-40 years for three individuals (75%) and 41-50 years for one individual (25%). Among the four patients, only one (25%) was nulliparous, while three (75%) were multiparous. One (25%) patient was diagnosed in the first trimester, and three (75%) patients were diagnosed in the third trimester. One (25%) patient was diagnosed at stage 1, one (25%) patient was diagnosed at stage 3, and two (50%) patients were diagnosed at stage 4. Two (50%) patients had the luminal A subtype, one (25%) patient had the luminal B Her2 positive subtype, and one (25%) patient had the luminal B Her2 overexpression subtype. Three (75%) patients underwent delivery by caesarean section, and one (25%) patient underwent laparotomy for fetal evacuation. According to gestational age, there were four (100%) cases of premature delivery. Among the four deliveries, all babies (100%) were born with low birth weight (<2,500 grams). The characteristics of the four patients in this study were that all were over 35 years of age, and all babies were born with low birth weight. Timely detection allows for early treatment, which can improve outcomes for both the mother and the developing fetus.